Chronic generalized pruritus without primary skin lesions: a longitudinal prospective observational study. (24th July 2018) - Alizadeh, Narges; Mirpour, Seyyed Hossein; Golmohamadi, Razieh; Darjani, Abbas; Eftekhari, Hojat; Rafiei, Rana; Gharaei Nejad, Kaveh; Azimi, Seyyede Zeinab
Abstract: Pruritus is among the most common complaints in the field of dermatology. It is also a disturbing symptom of many systemic disorders. Chronic pruritus (CP) refers to the cases of the symptom which last longer than 6 weeks. We conducted a prospective analysis of patients with generalized pruritus without primary skin lesions. All patients underwent primary evaluations and then were followed from 12 to 18 months for further evaluations. Of the 5, 127 patients referred to our dermatology clinic, 49 patients with generalized pruritus without primary skin lesions were evaluated. Most of the patients (44%) were in the age group of 40–60 years and female (58%). The duration of pruritus was 37.04 ± 30.4 weeks. Fifty percent of the patients with generalized pruritus had a systemic cause of pruritus. The most common underlying diseases were thyroid disorders (16.67%), diabetes mellitus (12.5%), and malignancy (8.33%). There were no significant statistical differences among the patients in terms of their age, gender, and disease duration with the underlying diseases ( P = 0.47, P = 0.99, P = 0.816, respectively). However, the average age of the onset of pruritus was 12 years earlier in the women regardless of the underlying diseases ( P = 0.011). Based on the findings of the study, we recommend considering endocrine disorders and malignancies as the most common underlying diseases leading to chronic pruritus without primary skin lesions.